Intraoral cysticercosis of the masseter muscle- A rare finding; correlation of histopathology with MRI and USG - Shrestha, M; Shakya, P; Shrestha, S (Journal of Chitwan Medical College, 2014)
Cysticercosis refers to infection of tissues after exposure of eggs of pork tapeworm Taenia solium. The authors report a rare case of a solitary intraoral cysticercosis in a thirty-four year female who presented with a mass in the left buccal mucosa of two months duration. The attending dentist could not have an impression of the lesion and sent for ultrasonography. The ultrasonographic report described a well defined hypoechoic lesion with central hypoechoic mural nodular area in left buccal region with muscle plane along with posterior enhancement suggestive of cystic nature. The impression was of benign cystic lesion in left buccal region (muscle plane). The MRI report revealed a 12 mm diameter T2 high signal intensity area noted in the anterior aspect of the left masseter muscle that showed iso to low signal in T1 weighted images. An ill marginated T2 high signal intensity was seen in left masseter muscle which also showed slight enlargement. The impression was of cystic lesion in left masticator space with edema in surrounding soft tissue plane. The lesion was enucleated and the histological findings revealed a cystic lesion containing parasitic larva. The cystic cavity was surrounded by a collagenous capsule of multinucleated foreign body giant cells with admixture of lymphocytes, plasma cells and histiocytes. The parasitic larva showed thick integument with projections and a myxomatous inner stroma. Thus a definitive diagnosis of “oral cysticercosis” was given. Oral cysticercosis rarely involves the oral cavity. This case reports a rare involvement of cysticercosis involving the masseteric space. DOI: http://dx.doi.org/10.3126/jcmc.v4i2.10864 Journal of Chitwan Medical College 2014; 4(2): 44-47